Effect of central metal ion on molecular dipole in porphyrin self-assembled monolayers - Rao, Manohar (2013)
The physical and electronic properties of nano-scale semiconductor devices are mainly decided by their surfaces and interfaces. Use of dipolar self-assembled monolayer (SAM) on semiconductor/oxide interfaces has an enormous potential to tailor the behavior of nanoelectronic, optical and biological devices. Among different molecules, porphyrins have been identified to form chemically stable SAMs on different substrates and their dipolar properties can be tuned by incorporating various metal species in them. This allows work-function tuning according to various technological needs. In this paper, we describe the effect of central metal ion (selected period-4 transition metal ions Zn, Cu, Ni, Fe and Co) incorporated in 5-(4-hydroxyphenyl)-10,15,20-tri(p-tolyl)porphyrin (TTPOH) on the surface potential using Kelvin probe microscopy. Density functional theory (DFT) calculations were performed to estimate the magnitude of dipole moments. Also, absorption spectra of TTPOH molecule and its metal derivatives are compared.